2021
DOI: 10.1186/s40545-021-00384-x
|View full text |Cite
|
Sign up to set email alerts
|

Value of pharmacy services upon admission to an orthopedic surgery unit

Abstract: Background In Lebanon, the role of the pharmacist remains underestimated in the medication reconciliation process, especially in surgical departments. This study aims to assess the impact of pharmacist-conducted medication reconciliation performed within 48 h of hospital admission to the orthopedic surgical department. Methods This was a prospective single-arm study conducted in a tertiary-care teaching hospital in Lebanon between October 2019 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Ouweini et al reported the impact of pharmacist-led MR within 48 h of orthopedic admission for surgical treatment [22], and found that 84.5% of interventions based on pharmacist-led MR were accepted by surgical residents and fellows. In contrast, in a prospective cohort study of adult patients admitted to the emergency department, pharmacist-led MR was conducted prior to the preparation of a physician's admission order.…”
Section: Discussionmentioning
confidence: 99%
“…Ouweini et al reported the impact of pharmacist-led MR within 48 h of orthopedic admission for surgical treatment [22], and found that 84.5% of interventions based on pharmacist-led MR were accepted by surgical residents and fellows. In contrast, in a prospective cohort study of adult patients admitted to the emergency department, pharmacist-led MR was conducted prior to the preparation of a physician's admission order.…”
Section: Discussionmentioning
confidence: 99%
“…A szabályzat értelmében a gyógyszerészek koordinálják a folyamatban résztvevő összes egészségügyi szakember multidiszciplináris oktatását. 40 Egy másik tanulmányban arra a következtetésre jutottak, hogy a klinikai gyógyszerészek teljesebb és pontosabb gyógyszeranamnézist készítenek, mint az ápolók, ami csökkentheti a fekvőbetegeknél a nemkívánatos gyógyszerhatások létrejöttét. Figyelembe véve, hogy az ortopédiai fekvőbetegek körében milyen gyakoriak a gyógyszerelési hibák, a klinikai gyógyszerészek által végzett gyógyszerészi gondozás fontos szerepet játszhat az ellátás javításában.…”
Section: A Klinikai Gyógyszerészi Gondozás Az Ortopédiábanunclassified
“…As new technologies are added to therapeutic care, pharmacists must acquire new knowledge, skills, and behaviors to be able to apply new modalities to patient care [ 2 ]. Furthermore, pharmacists are no longer solely responsible for drug dispensing; they now play an essential role in community health and wellness through expanded services, such as educational counseling [ 3 ], medication safety [ 4 ], and medication reconciliation and management [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%